10(z+1)-4(z-1)=2(z-2)+3(z-3)

Simple and best practice solution for 10(z+1)-4(z-1)=2(z-2)+3(z-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(z+1)-4(z-1)=2(z-2)+3(z-3) equation:


Simplifying
10(z + 1) + -4(z + -1) = 2(z + -2) + 3(z + -3)

Reorder the terms:
10(1 + z) + -4(z + -1) = 2(z + -2) + 3(z + -3)
(1 * 10 + z * 10) + -4(z + -1) = 2(z + -2) + 3(z + -3)
(10 + 10z) + -4(z + -1) = 2(z + -2) + 3(z + -3)

Reorder the terms:
10 + 10z + -4(-1 + z) = 2(z + -2) + 3(z + -3)
10 + 10z + (-1 * -4 + z * -4) = 2(z + -2) + 3(z + -3)
10 + 10z + (4 + -4z) = 2(z + -2) + 3(z + -3)

Reorder the terms:
10 + 4 + 10z + -4z = 2(z + -2) + 3(z + -3)

Combine like terms: 10 + 4 = 14
14 + 10z + -4z = 2(z + -2) + 3(z + -3)

Combine like terms: 10z + -4z = 6z
14 + 6z = 2(z + -2) + 3(z + -3)

Reorder the terms:
14 + 6z = 2(-2 + z) + 3(z + -3)
14 + 6z = (-2 * 2 + z * 2) + 3(z + -3)
14 + 6z = (-4 + 2z) + 3(z + -3)

Reorder the terms:
14 + 6z = -4 + 2z + 3(-3 + z)
14 + 6z = -4 + 2z + (-3 * 3 + z * 3)
14 + 6z = -4 + 2z + (-9 + 3z)

Reorder the terms:
14 + 6z = -4 + -9 + 2z + 3z

Combine like terms: -4 + -9 = -13
14 + 6z = -13 + 2z + 3z

Combine like terms: 2z + 3z = 5z
14 + 6z = -13 + 5z

Solving
14 + 6z = -13 + 5z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-5z' to each side of the equation.
14 + 6z + -5z = -13 + 5z + -5z

Combine like terms: 6z + -5z = 1z
14 + 1z = -13 + 5z + -5z

Combine like terms: 5z + -5z = 0
14 + 1z = -13 + 0
14 + 1z = -13

Add '-14' to each side of the equation.
14 + -14 + 1z = -13 + -14

Combine like terms: 14 + -14 = 0
0 + 1z = -13 + -14
1z = -13 + -14

Combine like terms: -13 + -14 = -27
1z = -27

Divide each side by '1'.
z = -27

Simplifying
z = -27

See similar equations:

| 27x+4=18x+1 | | 10(z+1)-4(z-1)=2(z-2)+(z-3) | | 10-3x=24+4x | | 13(3x-5)=6x-4 | | 20+r=r-2(3r+3) | | 5a-b=1 | | K-e=m | | 7x+7=121 | | 3n-4=45 | | Sin^2(x)=3vos^2x | | 7x^2-9x-6=8 | | 4x+23=39 | | 4x^2-9x-6=8 | | 10=3n+4 | | 12p+10p=-11 | | (2z-4)=8 | | (3r+3)(2)= | | 9x-1+4x-14=180 | | 6(X+2)+2(X-4)+3=7 | | 2r^2+48=22r | | 4x+y=360 | | 5(2x-7)-2=5(x-4)+18 | | 8a+9+4a-5= | | sinx+2*sinx*cosx=0 | | -8=2(8-6m) | | 6X+12*2X-11=7 | | 22+3x=119.5 | | 65=80c+49 | | 2x+36=6x+8 | | y^3+3y^2=25y+75 | | 8x-5=400 | | 5a+2b+6a-2b= |

Equations solver categories